Effect of implementing the NEWS2 escalation protocol in a large acute NHS trust: a retrospective cohort analysis of mortality, workload and ability of early warning score to predict death within 24 hours. Issue 11 (24th November 2022) - Forster, Sarah; McKeever, Tricia M; Shaw, Dominick
Abstract : Objectives: To describe the inpatient population, establish patterns in admission and mortality over a 4-year period in different cohorts and assess the prognostic ability and workload implications of introducing the National Early Warning Score 2 (NEWS2) and associated escalation protocol. Design: Retrospective cohort analyses of medical and surgical inpatient admissions. Setting: Large teaching hospital with tertiary inpatient care and a major trauma centre employing an electronic observations platform, initially with a local early warning score, followed by NEWS2 introduction in June 2019. Participants: 332 682 adult patients were admitted between 1 January 2016 and 31 December 2019. Outcome measures: Mortality, workload and ability of early warning score to predict death within 24 hours. Results: Admissions rose by 19% from 76 055 in 2016 to 90 587 in 2019. Total bed days rose by 10% from 433 382 to 477 485. Mortality fell from 3.7% to 3.1% and was significantly lower in patients discharged from a surgical specialty, 1.0%–1.2% (p<0.001). Total observations recorded increased by 14% from 1 976 872 in 2016 to 2 249 118 in 2019. 65% of observations were attributable to patients under medical specialties, 34% to patients under surgical specialties. Recorded escalations to the registrar were stable from January 2016 to May 2019 but trebled following the introduction of NEWS2 in June 2019. Conclusions: There was an increase in hospital inpatient activity between 2016 and 2019, associated with a reduction in mortality and percentage of observations calculated as reaching threshold NEWS2 score of 7 for escalation to the registrar. The introduction of the NEWS2, with a higher sensitivity and lower specificity, when allied to its escalation protocol, was associated with a significant increase in actual recorded escalations to the registrar. This was more marked in the surgical population and would support refining threshold scores based on admission characteristics when developing the next iteration of NEWS.